2021
DOI: 10.3389/fonc.2021.610952
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Feasibility of Programmed Death-1/Programmed Death Ligand-1 Blockade Therapy in Non-Small Cell Lung Cancer Patients With High Antinuclear Antibody Titers

Abstract: BackgroundImmune checkpoint inhibitor (ICI) therapy has been described to markedly improve patient survival. However, reports describing the antitumor therapeutic efficacy and safety of ICIs in patients with autoantibodies are scarce.MethodsThis study examined the efficacy and feasibility of ICIs in antinuclear antibody (ANA)-positive patients with non-small cell lung cancer (NSCLC). An ANA titer greater than 1:40 and 1:80 was defined as positive and high, respectively. Patients who were treated with ICIs at S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 25 publications
4
23
0
Order By: Relevance
“…To date, the majority of published studies that evaluated different autoantibodies as biomarkers for safety and efficacy of ICI treatment were conducted in advanced or metastatic NSCLC patients. 18,[21][22][23][24][25] Two studies considered additional autoantibodies besides ANA. Toi et al 23 retrospectively analyzed 137 patients with NSCLC and found out that individuals with preexisting antibodies (ANA, rheumatoid factor, antithyroglobulin, antithyroid peroxidase) at treatment initiation had more favorable outcome as indicated by PFS as compared to patients without antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the majority of published studies that evaluated different autoantibodies as biomarkers for safety and efficacy of ICI treatment were conducted in advanced or metastatic NSCLC patients. 18,[21][22][23][24][25] Two studies considered additional autoantibodies besides ANA. Toi et al 23 retrospectively analyzed 137 patients with NSCLC and found out that individuals with preexisting antibodies (ANA, rheumatoid factor, antithyroglobulin, antithyroid peroxidase) at treatment initiation had more favorable outcome as indicated by PFS as compared to patients without antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…( 8 ) reported metastatic NSCLC patients positive for ANA had significantly prolonged PFS and OS, which contradicts the conclusion reached by another study ( 7 ). The other two studies ( 5 , 6 ) suggested that the efficacy and safety of ICIs therapy in patients with NSCLC and positive ANA were comparable to those negative for ANA. Accordingly, there was no significant difference in the incidence of irAEs, ORR, and survival outcome between the 16 NSCLC patients positive for ANA and 30 NSCLC patients negative for ANA retrieved from our cohort (data not shown).…”
Section: Discussionmentioning
confidence: 95%
“…As for the effect of ANA titer, the study of Mouri et al. ( 5 ) suggested the incidence of irAEs was not significantly different between the ANA-positive and ANA-negative groups, regardless of the cutoff of ANA titers (1:40 or 1:80). Our results also reached the similar conclusion that patients with preexisting ANA had no increased risk of irAEs, regardless of the cutoff of ANA titers (1:80 or 1:160) (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations